IMPROVING EFL LEARNERS’ LISTENING SKILLS BY USING AUDIO VISUAL AIDS - FEBRIANI, HANURA; ASVIO, NOVA; RAHMADONI, JEFRIL; VIVEKANANTHARASA, RAVEENTHIRAN (Linguists : Journal of Linguistics and Language Teaching, 2022)
The purpose of this research is find out how audio-visual aid can enhance students listening skills of EFL learners. From the observation, it was found that most students have bad scores in listening skills and low motivation in following listening materials. The researchers, then, employed the classroom action research method to fix the problem directly. This research was conducted in the English department of UIN FAS Bengkulu. The population used by the researchers was students in the third semester who got listening class. The sampling technique used was purposive sampling, choosing the criteria or specific considerations so that they do not go through the selection process as done in a random technique. In this case, the researchers chose class 3b because it had the lowest grades and motivation among the other classes. Two cycles were done to handle the problem. The instrument used to gain the data by using a test, observation sheet, and interview. The data comparison from pre-assessment to final assessment shows a positive impact of the strategy on students' scores and motivation in the teaching-learning process of listening.